The Role of Service and System Quality in Enhancing User Satisfaction in Digital Systems - Sukma Alfandia, Nurlita; Arifafarina, Raissa (Profit: Jurnal Adminsitrasi Bisnis, 2026)
This study investigates the influence of system quality and service quality on user satisfaction by applying for tax, namely MSME owners, and extending the DeLone and McLean IS Success Model. Using a quantitative approach, we analyze user perceptions of usability, responsiveness, and support across various IS environments. The study population was all Micro, Small, and Medium Enterprises (MSMEs). Convenient sampling was used, with a sample size of 100 questionnaires. The results indicate that system and service quality significantly influence user satisfaction. System quality, particularly usability and reliability, emerged as strong predictors of satisfaction, while service quality contributed through effective support and communication. These findings underscore the importance of integrating user feedback into the design and improvement process, which fosters user engagement and system acceptance. Practical implications suggest developers prioritize user-centered design, while organizational leaders should foster a culture that values continuous improvement and user support. This study contributes to the IS literature by strengthening the relevance of quality dimensions in digital transformation. Future research could expand on these findings by exploring demographic-specific effects and incorporating new variables such as trust and adaptability into the IS success framework.